Pengelolaan Kenakalan Siswa di SMK Pancasila Purwodadi - Feriyanti, Erika, Prof. Dr. Sutama, M.Pd, Dr.Suyatmini,SE.,M.Si (2016)
Erika Feriyanti. Q 100140056. Manajement of Students Misbehaviorat Vocational High School Pancasila Purwodadi. Thesis. Education Administration. Postgraduate Education. University of Muhammadiyah Surakarta. 2016 The purpose of the research to describe the managementof Students Misbehavior, to described the kind of management of student misbehavior and to described the management of how to cope white student misbehavier on vacational school pancasila purwodadi. The kind of qualitative research white etnography's design. The placed for the research at vacational school pancasila purwodadi. The time of the research strated from august until fecruary. The research subject was the head master, teachers, management team of misbehavior, and students. The method of data accumulated white observation, interviews, and documentation. Thevalidity of data using a triangulasi system. The data analysis techniques was using data accumulated, data reduction, data presentation, and conclusion. The result of the research (1) management of student misbehavior white providing guidance for the student every counceling lesson about the rule, the order, and the impact (2) the kind of management of student misbehavior is cooperation white the student's parent, all of the school component, and the local officials (3) the management of how to cope white student misbehavior white improve the ability of the student in a particular field suitable white the ability and talents each of the student use the extracurricular. Keywords: management, teeneger misbehavior, vocational schools